Emiliania huxleyi—Bacteria Interactions under Increasing CO2 Concentrations - Joana Barcelos e Ramos; Susana Chaves Ribeiro; Kai George Schulz; Francisco José Riso Da Costa Coelho; Vanessa Oliveira; Angela Cunha; Newton Carlos Marcial Gomes; Colin Brownlee; Uta Passow; Eduardo Brito de Azevedo (Microorganisms, 2022)
The interactions established between marine microbes, namely phytoplankton–bacteria, are key to the balance of organic matter export to depth and recycling in the surface ocean. Still, their role in the response of phytoplankton to rising CO2 concentrations is poorly understood. Here, we show that the response of the cosmopolitan Emiliania huxleyi (E. huxleyi) to increasing CO2 is affected by the coexistence with bacteria. Specifically, decreased growth rate of E. huxleyi at enhanced CO2 concentrations was amplified in the bloom phase (potentially also related to nutrient concentrations) and with the coexistence with Idiomarina abyssalis (I. abyssalis) and Brachybacterium sp. In addition, enhanced CO2 concentrations also affected E. huxleyi’s cellular content estimates, increasing organic and decreasing inorganic carbon, in the presence of I. abyssalis, but not Brachybacterium sp. At the same time, the bacterial isolates only survived in coexistence with E. huxleyi, but exclusively I. abyssalis at present CO2 concentrations. Bacterial species or group-specific responses to the projected CO2 rise, together with the concomitant effect on E. huxleyi, might impact the balance between the microbial loop and the export of organic matter, with consequences for atmospheric carbon dioxide.